TRACCIARE UN LABIRINTO DI MAIS CON IL GPS Il caso del Labirinto di HORT (GEOmedia, 2018)
This job comes from a need of HORT of Ancona, a company born as a spin-off of Università  Politecnica delle Marche, and which now provides agronomic services, to look for an innovative method to layout the path of a corn labyrinth on the field, a recreational-educational activity of which HORT is a specialist, as it is about to inaugurate the sixth edition, this year in Senigallia as well, Marche Region.HORT needed a new solution that would allow it to avoid performing ‘alignment and squares' operations with old-fashioned optical instruments, and speed up manual path tracking, a solution that was found with Topcon Positioning Italy's contribution through the use of modern, multi-constellation GPS receivers.